Advances on Practical Applications of Agents and Multi-Agent Systems 11th International Conference, PAAMS 2013, Salamanca, Spain, May 22-24, 2013. Proceedings - Demazeau, Yves.; Ishida, Toru.; Corchado, Juan M.; Bajo, Javier; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 11th International Conference on Practical Applications of Agents and Multi-Agent Systems, PAAMS 2013, held in Salamanca, Spain, in May 2013. The 14 revised full papers and 9 short papers presented together with 16 demonstrations were carefully reviewed and selected from 70 submissions. The papers report on the application and validation of agent-based models, methods, and technologies in a number of key application areas, including: agents for real world problems; crowd modeling and analysis; decision making and discovery; interaction with artificial agents; mobility, ubiquity and clouds; (multi-)agent design technology; and simulation and organization.
Application and validation of agent-based models, methods, and technologies in a number of key application areas -- agents for real world problems -- crowd modeling and analysis -- decision making and discovery -- interaction with artificial agents -- mobility, ubiquity and clouds -- (multi-)agent design technology -- simulation and organization.
Keywords: Computer science; Artificial intelligence; Computer simulation; Education; Computer Science; Artificial Intelligence (incl. Robotics).; Simulation and Modeling; Computers and Education; Computers and Society; Computer Applications